Visualisasi Wanita dalam Al-Qur’an: Penerapan Pendekatan Interpretasi Teks Nashr Hamid Abu Zayd - Muhammad Furqon; Kerwanto Kerwanto; Muh. Adlan Nawawi (Student Scientific Creativity Journal, 2023)
Women are often identified with a beauty, as is the case in the selection of the language style of the Qur'an. The diction used by the Qur'an in visualizing women, starting from their creation, association with an angel, as well as the description of their physical characteristics show how noble and honorable they are. The glory of the woman is a symbol of liberation from dehumanization and discrimination against women in jahiliyah and a form of human equality in the eyes of Allah Swt. The purpose of this study was to determine the concept of text interpretation in comprehensively interpreting women and to know the comparison of the formulation of classical interpretation and modern interpretation of the existence of women in the Qur'an and to know what the formulation of intertextuality of the verses visualizing women. The method in this study uses library research that focuses on library data, which are primary sources to classical commentaries and works of Nasr Hamid Abu Zayd as one of the figures of "hermeneutics of liberation" and other secondary sources. The results of this study concluded related agrumen Nashr Hamid Abu Zayd regarding the Qur'an is a cultural product, the author is more inclined to the opinion of Quraish Shihab, that the Qur'an is kalâmullah, not a creature. The concept of interpretation of the text of Nasr Hamid Abu Zayd in reading the verses visualizing women in the Qur'an is to do a more in-depth reading by prioritizing objectivity and considering the historical and socio-cultural facts from which the text of the Qur'an was revealed. This study has implications in reconstructing the pattern of inheritance relay understandings of women in the verses visualization of women who tend to the interpretation and understanding of patriarchal bias.